Adverse effects of immune-checkpoint inhibitors: epidemiology, management and surveillance - Martins, Filipe; Sofiya, Latifyan; Sykiotis, Gerasimos P; Lamine, Faiza; Maillard, Michel; Fraga, Montserrat; Shabafrouz, Keyvan; Ribi, Camillo; Cairoli, Anne; Guex-Crosier, Yan; Kuntzer, Thierry; Michielin, Olivier; et al. (Nature reviews. Clinical oncology, 2019)
Immune-checkpoint inhibitors (ICIs), including anti-cytotoxic T lymphocyte antigen 4 (CTLA-4), anti-programmed cell death 1 (PD-1) and anti-programmed cell death 1 ligand 1 (PD-L1) antibodies, are arguably the most important development in cancer therapy over the past decade. The indications for these agents continue to expand across malignancies and disease settings, thus reshaping many of the previous standard-of-care approaches and bringing new hope to patients. One of the costs of these advances is the emergence of a new spectrum of immune-related adverse events (irAEs), which are often distinctly different from the classical chemotherapy-related toxicities. Owing to the growing use of ICIs in oncology, clinicians will increasingly be confronted with common but also rare irAEs; hence, awareness needs to be raised regarding the clinical presentation, diagnosis and management of these toxicities. In this Review, we provide an overview of the various types of irAEs that have emerged to date. We discuss the epidemiology of these events and their kinetics, risk factors, subtypes and pathophysiology, as well as new insights regarding screening and surveillance strategies. We also highlight the most important aspects of the management of irAEs.